Moving Beyond Medication: Harnessing the Power of Physical Therapy and Dance Therapy in Parkinson’s Disease Management - Adamiec, Ksawery; Trojanowski, Dominik; Rodak, Małgorzata; Smorońska-Rypel, Joanna; Szymczuk, Błażej; Kajzar, Magdalena; Nitka, Kamila; Iwan, Magdalena; Piątkowska, Natalia; Milczarek, Jakub (Quality in Sport, 2024)
Introduction Parkinson’s disease (PD) poses significant challenges due to its complex array of motor and non-motor symptoms, impacting patients’ quality of life. While traditional pharmacological treatments focus on motor symptoms, non-pharmacological interventions, including physical and dance therapy, offer alternative approaches. Aim of the Study This study aims to evaluate the therapeutic potential of physical and dance therapy, including tango, in managing motor symptoms and improving overall well-being in individuals with PD. It seeks to compare these interventions with traditional treatments and explore their efficacy. State of Knowledge Parkinson’s disease management involves a combination of pharmacological and non-pharmacological approaches. Traditional treatments target motor symptoms but have limitations. Non-pharmacological interventions, such as deep brain stimulation and physical therapy, complement traditional treatments. Dance therapy, including tango, shows promise in improving motor function and quality of life. Conclusions Physical and dance therapy, including tango, offer promising avenues for managing motor symptoms and enhancing quality of life in PD patients. While traditional treatments remain essential, non-pharmacological interventions provide valuable alternatives. Further research is needed to refine intervention parameters and compare their effectiveness comprehensively. Overall, these therapies present holistic approaches to PD management, addressing both motor and non-motor symptoms for improved patient outcomes.